Dysregulation of innate cell types in the hepatic immune microenvironment of alcoholic liver cirrhosis - Ren, Ao; He, Wenjing; Rao, Jiawei; Ye, Dongmei; Cheng, Pengrui; Jian, Qian; Fu, Zongli; Zhang, Xuzhi; Deng, Ronghai; Gao, Yifang; Ma, Yi (Frontiers in Immunology, 2023)
Introduction The risk of alcoholic cirrhosis increases in a dose- and time-dependent manner with alcohol consumption and ethanol metabolism in the liver. Currently, no effective antifibrotic therapies are available. We aimed to obtain a better understanding of the cellular and molecular mechanisms involved in the pathogenesis of liver cirrhosis. Methods We performed single-cell RNA-sequencing to analyze immune cells from the liver tissue and peripheral blood form patients with alcoholic cirrhosis and healthy controls to profile the transcriptomes of more than 100,000 single human cells and yield molecular definitions for non-parenchymal cell types. In addition, we performed single-cell RNA-sequencing analysis to reveal the immune microenvironment related to alcoholic liver cirrhosis. Hematoxylin and eosin, Immunofluorescence staining and Flow cytometric analysis were employed to study the difference between tissues and cells with or without alcoholic cirrhosis. Results We identified a fibrosis-associated M1 subpopulation of macrophages that expands in liver fibrosis, differentiates from circulating monocytes, and is pro-fibrogenic. We also define mucosal-associated invariant T (MAIT) cells that expand in alcoholic cirrhosis and are topographically restricted to the fibrotic niche. Multilineage modeling of ligand and receptor interactions between the fibrosis-associated macrophages, MAIT, and NK cells revealed the intra-fibrotic activity of several pro-fibrogenic pathways, including responses to cytokines and antigen processing and presentation, natural killer cell-mediated cytotoxicity, cell adhesion molecules, Th1/Th2/Th17 cell differentiation, IL-17 signaling pathway, and Toll-like receptor signaling pathway. Discussion Our work dissects unanticipated aspects of the cellular and molecular basis of human organ alcoholic fibrosis at the single-cell level and provides a conceptual framework for the discovery of rational therapeutic targets in liver alcoholic cirrhosis.